Ultrasonic Image Compounding Method Based on the Instantaneous Phase Image - Prado, Vander Teixeira; Higuti, Ricardo Tokio [UNESP]; IEEE (Ieee, 2016)
The quality of ultrasonic images depends on array configuration, image beamforming algorithm, propagation modes and signal-to-noise ratio. Some alternatives to improve image quality are related to the use of coherence weighting factors and image compounding techniques. This work proposes an image compounding method based on the Instantaneous Phase (IP) image. From the analysis of this image and the application of the respective threshold, a coherence weighting factor is created, which is multiplied by the conventional amplitude images to reduce artifacts and improve contrast. The images are then combined according to the indication of the presence of reflectors in the IP image. The method was experimentally tested on an aluminum plate with artificial defects. As result artifacts and dead zone are reduced, and contrast and defects detection are improved.
Keywords: Image compounding technique; Instantaneous phase; Ultrasound